Adding Value with Benefit-Cost Analysis: Forecasting Net Social Benefit from Impacts of Slot Machine Gambling in Maryland. Issue 2 (19th August 2015) - Farrow, Scott
Abstract : The estimated impacts, benefits, and costs of legalizing slot machines in Maryland are analyzed building on and contrasting with results from an impact analysis. The analysis provides estimates of the components and the total net benefits to the state and its citizens; the role of uncertainty, distributional impacts, and a basic tax alternative. The results forecast mostly positive net benefits for Maryland both in comparison to doing nothing and in comparison to raising an equivalent amount in taxes. However, if slot revenue raised from the lower income population is given more weight, then doing nothing or raising taxes appears to be preferred.